(untitled) (Journal of Bangladesh Academy of Sciences, 2021)
The radioactivity of naturally occurring radionuclides 226Ra, 232Th, and 40K was determined in thirteen cement samples collected from different manufactures of Dhaka city. The measurement was performed by gammaray spectrometry system using high purity germanium (HPGe) detector. The average activity of 226Ra, 232Th, and 40K in cement samples are fon und to be 30.23±15.04 Bqkg-1, 20.10±11.76 Bqkg-1 and 145.27±24.14 Bqkg-1, respectively. The average values of radium equivalent activity (Raeq), absorbed dose rates (D), internal hazard and external hazard index (Hex), and annual effective dose equivalent are 370 Bqkg-1, 0.27, 0.18, and 27.99 nGyh-1, respectively. The average annual effective dose is found 0.13 mSvy-1, which is less than the recommended value (1 mSvy-1) by the International Commission on Radiological Protection (ICRP-60, 1990), as the maximum permissible annual effective dose to the members of the public. The present study results are discussed and compared with those reported in similar studies and with internationally recommended values. No artificial radioactivity was found in the present study. The results show that the analyzed cement samples do not pose any significant radiation hazard from naturally occurring radionuclides 226Ra, 232Th and 40K reported here and also considered safe for use in buildings construction. J. Bangladesh Acad. Sci. 45(1); 95-104: June 2021